OC-029 Phenotype of Human Intrahepatic Innate Lymphoid Cell Subsets in Heatlh and Disease. (17th August 2016) - McDowell, P; Roberts, S; Jeffery, HC; Hunter, S; Oo, YH
Abstract : Introduction: Innate lymphoid cells (ILCs) involve in the initiation, regulation and resolution of inflammation. Although the role of ILCs in murine liver fibrosis and biliary proliferation has been reported, the phenotypic characteristics and functional role of these cells in human liver disease remains undefined. We explored the detailed phenotype of human intrahepatic ILCs to gain insight on their function. Methods: Liver infiltrating lymphocytes from normal liver tissue, autoimmune liver diseases (AILD), alcoholic liver disease (ALD) and non-alcoholic steatohepatitis (NASH) explants were phenotyped with flow cytometry. Results: Total intrahepatic ILC (CD3 − lineage − CD45 − CD127 + ) comprised 1% (IQR 0.4–1.7%) of the CD3 − CD45 + population in normal liver and 0.4% for ALD/NASH and autoimmune livers. The ILC1 subset constituted the majority of intrahepatic ILC and its frequency is higher in normal liver compared to diseased livers (85% vs. 67%) (p < 0.05). In contrast, CD161 + CRTH2 + ILC2 subset and ILC3 subset frequency are higher in diseased livers compared to normal livers. Interestingly, frequency of ILC3 is significantly higher in ALD compared to normal liver (p < 0.01). Intrahepatic ILC subsets are in activated and tissue resident state (CD69 75–90%). All subsets expressed the liver tissue homing chemokine receptor, CXCR3. Expression frequency is highest on diseased ILC1 (AILD 50%, ALD/NASH 56%, ) compared to ILC2 (AILD 24%; ALD/NASH 15%) and ILC3 (AILD 38%, ALD/NASH 28%). Biliary tropic receptor CCR6 was expressed more highly by ILC subsets in diseased compared to normal livers. The fibronectin receptor, VLA5 and laminin receptor VLA6 were both highly expressed on all intrahepatic ILC subsets (60–90% and 55–80% respectively). In terms of the cytokine receptors expressed, on all ILC subsets, IL-6R was near undetectable (2%) and low expressions of ST2 (3–6%), IL-25R (2–5%) and IL-23R (2–7%) were detected. In contrast there was almost ubiquitous expression of IL18Ralpha. CD25 was also very highly expressed. Of note, CD25 was significantly higher in ILC1 and ILC3 subsets from normal compared to AILD (p < 0.01) livers (40% vs. 80%; 66% vs. 93%) while intrahepatic ILC2 and ILC3 subsets in diseased states highly expressed CD25 (>90%). Of likely functional importance, intrahepatic ILC1 expressed IFN-γ (40%) while ILC2 expressed IL-13 (20–50%) in diseased states. Conclusion: We report for the first time the presence of all three ILC subsets within the human liver immune cell infiltrates. CXCR3 + IFN-γ expressing ILC1 subset is enriched in both normal and inflamed diseased livers. Higher frequencies of CCR6 + VLA5 + VLA6 + IL-13 expressing ILC2 are observed in diseased livers suggesting that this subset may play a role in biliary pathology and peri-biliary fibrosis. Disclosure of Interest: None Declared